Cerebral Aspergillosis in an Immunocompetent Patient: A Case Report (Bangladesh Journal of Infectious Diseases, 2018)
Aspergillus is a fungus found in the environment. In an immunocompetent person, inhalation of spores may cause localized infection. Invasive aspergillosis has a poor prognosis. We describe a case of cerebral aspergillosis in an immune competent patient. A 30-year-old man was admitted with seizures and headaches. Magnetic resonance imaging (MRI) of the brain showed contrast enhancing lesion at the suprasellar region. Excision biopsies showed granulomatous reactions, mixed inflammatory infiltration, fibrosis, and necro-purulent material mixed with fungal hyphae featuring acute-angle branching and septation, which was compatible with aspergillosis. Amphotericin B was begun. The results of testing for human immunodeficiency virus (HIV) was negative.  Unfortunately the patient died on twentieth post-operative day. Most cases of invasive aspergillosis show that this organism is pathogenic in immunocompromized patients; however, some case reports show that invasive aspergillosis may not be so rare in immunocompetent patients. In these patients, virulent and drug-resistant forms of Aspergillus may be responsible for the disease, and treatment with antifungal agents is often ineffective, so that surgical excision is required.Bangladesh Journal of Infectious Diseases 2017; 4(2):52-55